(untitled) (British Journal of Global Ecology and Sustainable Development, 2024)
Improvement of the method of creation and implementation of interactive electronic didactic materials. The meaning of the concept of creating electronic educational and didactic materials has been revealed. getting to know the ways of introducing students to professional practice.